Molecular Docking and Computational Analysis of Chemical Constituents of Tinospora cordifolia as Potential DPP-4 Inhibitors for Diabetes Management. - Bharadwaj, Nidhi; Das, Alok Bihari; Sunil, Reddy; Devi, Sonia; Kumar, Perli.Kranti; Bhadkariya, Santosh; Kakkar, Saloni; I A, Chethan (Journal of Neonatal Surgery, 2025)
Tinospora cordifolia, a well-known medicinal plant, has been traditionally used for its wide range of therapeutic properties, including antidiabetic effects. In this study, we investigated the potential of five key chemical constituents of Tinospora cordifolia—10-Hydroxycolumbin, 11-Hydroxymustakone, 20-Beta-Hydroxyecdysone, 8-Hydroxytinosporide, and AMRITOSIDE-A—as inhibitors of dipeptidyl peptidase-4 (DPP-4), a key enzyme in glucose metabolism. Molecular docking simulations were performed using AutoDock VINA, and the results were analyzed for binding affinity, hydrogen bonding, and hydrophobic interactions. Among the compounds tested, 8-Hydroxytinosporide showed the highest docking score (-9.0 kcal/mol) with extensive interactions, followed by 10-Hydroxycolumbin and 20-Beta-Hydroxyecdysone. The interactions of these compounds with DPP-4 suggest their potential as natural DPP-4 inhibitors. Although Amritoside-A and 11-Hydroxymustakone demonstrated weaker binding affinities, further optimization of these compounds could enhance their activity. This study provides valuable insights into the antidiabetic potential of Tinospora cordifolia and supports its exploration as a source of novel DPP-4 inhibitors for diabetes therapy.